Exploring The Attitudes Of Students Towards The Effectiveness Of Suicide Interventions – A Case Study Of A Selected Institution In South Africa - Ludaka, Namhla-Atabile; Kangéthe, Simon Murote (Journal of Ecohumanism, 2025)
This qualitative study examines the attitudes of university students at a selected South African institution regarding the effectiveness of current suicide interventions. The research uses a qualitative approach, utilising exploratory and descriptive designs and case studies. Data were gathered through twelve in-depth interviews. The study is guided by the person-centred theory, specifically client-centred therapy, developed by Carl Rogers. Results emphasise the necessity for tailored, student-centred strategies that incorporate cultural sensitivity and address known risk factors. Participants stressed the importance of a welcoming campus community and inclusive support resources. The findings suggest that by considering student viewpoints, offering a variety of support services, and fostering a friendly atmosphere, mental health professionals can enhance the effectiveness of interventions. The study recommends that interventions be contextualised, involve on-going student engagement, and undergo continuous assessment to better prioritise student mental health. By shedding light on student mental health issues via a context-sensitive lens, this study contributes reliable strategies for fostering resilience and well-being in higher education. It underscores the value of student involvement in designing and evaluating interventions, thereby advancing scholarship on culturally responsive and effective suicide prevention in academic settings.